Hydrodynamics of narrow-tube fixed bed reactors filled with Raschig rings. (January 2020) - Moghaddam, E.M.; Foumeny, E.A.; Stankiewicz, A.I.; Padding, J.T.
Graphical abstract: Highlights: RBD-CFD approach is validated for modeling hydrodynamics in tortuous structures. Local flow structure and pressure drop in packings of Raschig rings are studied. Large deviation of azimuthally-averaged velocity profile from local velocity data. The method assists furthering the design of complexed packing systems. Abstract: The local flow structure and pressure drop in random packings of Raschig rings are analyzed using sequential Rigid Body Dynamics (RBD) method and Computational Fluid Dynamics (CFD) simulation. Tube-to-pellet diameter ratios, N, between 3 and 6 are investigated for laminar, transitional and turbulent flow regimes (5 ≤ Rep ≤ 3, 000). The computed pressure drops are in good agreement with the empirical correlation of Nemec and Levec (2005), while the Ergun equation exhibited high deviations of more than 60%, even when it is modified to explicitly account for non-sphericity of pellets. This deviation is ascribed to additional sources for eddy formation offered by Rashig rings, compared to spheres and cylinders, which cannot be counterbalanced by the usage of a higher specific surface area. The 3D results of flow structure demonstrate a large influence of packing topology on the velocity distribution: rings oriented parallel to the flow accelerate the local velocity through their axial holes, while rings oriented perpendicular to the flow provide additional space for vortex formation. The flow fields are substantially different from that found in packings of spheres and cylinders, both in terms of volume of backflow regions and velocity hotspots. This implies a higher order of local flow inhomogeneity in azimuthal and axial directions compared to spherical and cylindrical packings. Furthermore, it is found that azimuthal averaging of the 3D velocity field over the bed volume, which has been used to improve classical plug-flow pseudo-homogenous models to account for the role of tortuous velocity fields, cannot reflect the appearance of vortex regions and thereby leads to underestimation of the local axial velocity values by over 500% of the inlet velocity.